THE STATE OF TOXICOSIS IN PREGNANCY AND METHODS OF TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Pregnancy is a complex period in which many physiological and hormonal changes occur in a woman's body. During this process, many women face toxicosis of pregnancy. Toxicosis is a set of symptoms that develop during pregnancy and worsen the general condition of a woman. The main purpose of this article is to provide information about the manifestations, causes and treatment methods of toxicosis.